CE-43 Factors associated with neuropsychiatric involvement in 1193 latin american patients with systemic lupus erythematosus. (31st August 2016) - Barile-Fabris, Leonor A; Wojdyla, Daniel; Catoggio, Luis J; Scherbarth, Hugo R; Saurit, Verónica; Bonfa, Eloisa; Lavras Costallat, Lilian T; Cavalcanti, Fernando; Molina, José F; Reyes-Llerena, Gil; Massardo, Loreto; Amigo, Mary C; et al.
Abstract : Introduction: Neuropsychiatric (NP) manifestations in SLE are a major cause of morbidity, mortality and long term consequences. Factors related to their occurrence in patients with short disease duration, both early in the course of the disaease and during follow up have not been clearly established. Purpose: To identify disease and non-disease related factors associated with NP manifestations in early SLE. Methods: We included 1193 patients from the GLADEL inception cohort free of NP involvement at cohort entry. We examined the relationship between socio-demographic, clinical and laboratory data as well as disease activity and damage with NP involvement during follow-up. Data were recorded in ARTHROS database. We excluded all the secondary NP manifestations (metabolic, drug induced, infectious, etc). Statistical methods The time from cohort entry to first NP manifestation was examined using a Cox proportional hazard regression model. Patients without NP manifestations were censored at last study visit. Independent factors associated with NP involvement were identified using a multivariable Cox regression model. Variables included in the final model were selected using a backward selection algorithm with α-level to stay in the model set to 0.05. Results are summarised as hazard ratios with 95% confidence intervals. Results: During a median follow-up time of 52 months, 238 (20 %) patients had NP involvement. The cumulative incidence estimate of NP involvement at 1, 3 and 5 years was 8.3%, 17.8% and 24.7%, respectively. In the univariable analysis some variables like ethnic origin were found to be more frequent in mestizos as compared to patients in the other ethnic groups. Factors independently associated with NP manifestations during follow up are listed in Table 1 . Conclusions: There are both disease and non-disease related factors that are clearly associated with NP manifestations. Patients of Mestizo background, those with myositis and those with hemolytic anaemia are at higher risk of developing NP. Features Predictive of the Occurrence of NP Manifestations by Multivariable Cox regression model